PENGARUH HUMAN EROR TERHADAP AKURASI ARAH KIBLAT MASJID DAN KUBURAN DI KABUPATEN GOWA PROVINSI SULAWESI SELATAN - HL, Rahmatiah (ELFALAKY: Jurnal Ilmu Falak, 2020)
The effect of human error on the accuracy of the qibla direction of mosques and graves in Gowa regency aims to determine the percentage accuracy of the qibla direction of mosques and graves in Gowa district; To find out the causative factors so that the direction of the qibla of mosques and graves is less accurate so that we can find out the percentage of the influence of Human Error on the accuracy of the direction of Qibla and graves in Gowa Regency This study used a qualitative descriptive method and chose locations in mosques and cemeteries. The population in this study includes places of worship and burial places for Muslims in Gowa district. 1,174 mosques spread over 18 sub-districts. mosque and cemetery data samples represent the highlands, the capital of Gowa Regency, and the lowlands. Data collection methods include: participatory observation, in-depth interviews and documentation. The analysis method used is content analysis. Causes of human error Inadequate knowledge, lack of education and training, lack of imagination about the future, dependence on other parties, ignorance, negligence, and carelessness, lack of ability to communicate.Keywords: Qibla direction, human error, mosque and cemetery